2017
DOI: 10.1016/j.jpor.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between flipped classroom and team-based learning in fixed prosthodontic education

Abstract: Our previous study reported that TBL had higher efficiency than traditional style lecture. In the current study, there was no statistical difference in the examination score between flipped classroom and TBL. Therefore, we conclude that both styles are highly effective than traditional style lecture and constitute valid formats for clinical dental education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
77
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(88 citation statements)
references
References 13 publications
5
77
0
3
Order By: Relevance
“…The full texts were assessed using the eligibility criteria in phase 2, resulting in seven studies deemed suitable for further analysis. [19][20][21][22][23][24][25][26] Articles excluded in this phase and the reasons for exclusion are shown in Table 3. Therefore, a total of eight studies were included in the analysis ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The full texts were assessed using the eligibility criteria in phase 2, resulting in seven studies deemed suitable for further analysis. [19][20][21][22][23][24][25][26] Articles excluded in this phase and the reasons for exclusion are shown in Table 3. Therefore, a total of eight studies were included in the analysis ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…25 The efectiveness of lipped learning and conventional lectures was compared in ive studies; 19,21,22,25,26 three studies compared students' perceptions on lipped learning compared to conventional lectures; 19,21,22 and four studies assessed students' perceptions about lipped learning without comparison to another methodology. 20,[23][24][25] The MINORS tool was used to assess the methodological quality of the studies ( Table 4). The results showed that six studies had low RoB 19,[21][22][23][24]26 and two had moderate RoB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…42 When students were able to answer other student's questions encountered during self-study, they gained a higher sense of achievement and increased the motivation to learn. 26,43,44 The use of a point-awarding system within the Question and Discussion session played a vital role in the A J P E A c c e p t e d D r a f t success of the teaching strategy, as the students could be encouraged to learn, and improved performance because of being in competition with their peers. When the teacher randomly chose a student to answer on behalf of the group, each student would study harder.…”
Section: A J P E a C C E P T E D D R A F Tmentioning
confidence: 99%
“…12 The flipped classroom method has also been used successfully for teaching paediatric dentistry, 13 dental anatomy 14 and prosthodontics. 15 What is novel about the teaching described in this paper is that it employs virtual microscopy in a flipped classroom setting. Most of the published studies describing flipped classrooms in pathology have used videos as the online part of the classroom, after which students participated in learning activities designed to test knowledge acquisition.…”
mentioning
confidence: 99%